(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the increasing significance of self-education for students in the 21st century. It discusses how the rise of digital resources and online platforms has made self-directed learning a crucial supplement or alternative to traditional education. The benefits of self-education, such as flexibility, personalization, and the development of autonomy and confidence, are highlighted. The article also addresses the challenges of self-education, including the need for discipline and the ability to evaluate information. Finally, it considers the future of education, where the boundaries between formal and self-education are becoming increasingly blurred, and the value of self-taught skills in the academic and professional worlds